درجة ممارسة مدير المدرسة لدوره كمشرف تعليمي مقيم في المدارس المتوسطة الرسمية في قضاء صور من وجهة نظر المعلمين - جابر، ماجد محمد كامل (د محمد أمين الضناوي, 2023)
هدفت الدراسة إلى قياس درجة ممارسة مدير المدرسة لدوره كمشرف تعليمي مقيم في المدارس المتوسطة الرسمية في قضاء صور في لبنان من وجهة نظر المعلمين، ومعرفة ما إذا كان هناك تأثير لمتغيرات (الجنس، عدد سنوات الخبرة التعليمية، والوضع الوظيفي للمعلم) في درجات استجاباتهم. وللإجابة عن أسئلة الدراسة وتحقيق أهدافها، اعتمد المنهج الوصفي - المسحي من خلال بناء استبيان مكون من (56) فقرة موزعة على سبعة مجالات (المنهاج التعليمي، طرائق التعليم ووسائله، الإدارة الصفية، الإشراف على المعلمين، تقويم المتعلمين، معالجة المشكلات التحصيلية، النمو المهني للمعلمين)، ومن ثم توزيعه، بعد التأكد من درجة صدقه وثباته، على عينة مكونة من (328) معلما ومعلمة اختيروا بالطريقة العشوائية البسيطة. بينت نتائج الدراسة أن درجة ممارسة مدير المدرسة لدوره كمشرف تعليمي مقيم في المدارس المتوسطة الرسمية في قضاء صور جاءت متوسطة على المجالات الكلية، ومتوسطة، وبالترتيب تنازليا، على كل من المجالات: الإدارة الصفية، طرائق التعليم ووسائله، معالجة المشكلات التحصيلية، المنهاج التعليمي، تقويم المتعلمين، النمو المهني للمعلمين، في حين جاءت أدنى الممارسات وبدرجة منخفضة على مجال "الإشراف على المعلمين". كما أظهرت النتائج عدم وجود فروقات دالة إحصائيا عند مستوى دلالة (0.05) بين درجات استجابات المعلمين تعزى لكل من متغيرات الجنس، عدد سنوات الخبرة، والوضع الوظيفي للمعلم، وذلك حول درجة ممارسة مدير المدرسة لدوره كمشرف تربوي مقيم على كل من المجالات السبعة للاستبيان. في ضوء النتائج التي توصلت إليها، أوصت الدراسة بضرورة إلحاق مديري المدارس المتوسطة الرسمية ببرامج تدريبية لإكسابهم الكفايات (المعارف- المهارات) التي تمكنهم من ممارسة دورهم كمشرفين تربويين مقيمين بفاعلية، وكذلك أوصت الدراسة بضرورة تخفيف الأعباء الإدارية عن مدير المدرسة، وتوفير الموارد المالية والمادية والتجهيزات والوسائل التعليمية اللازمة للمدارس الرسمية. The study aimed to measure the degree of the school principal’s practice of his role as a resident educational supervisor in the public intermediate schools in the district of Tyre in Lebanon, from the teachers’ point of view, and to find out whether there is an effect of the variables (gender, number of years of educational experience, and the teacher’s job status) on the degrees of their responses. In order to answer the questions of the study, and achieve its objectives, a descriptive-survey approach was adopted by designing a questionnaire consisting of (56) items, distributed over seven fields (educational curriculum, methods and tools of education, classroom management, supervising teachers, evaluating learners, addressing achievement problems, professional growth of teachers), and then distributing it, after ascertaining the degree of its validity and reliability, to a sample of (328) male and female teachers who were chosen in a simple random way. The results of the study showed that the degree of the school principal’s practice of his role as an educational supervisor residing in the public intermediate schools in the district of Tyre was medium in the overall fields, and medium, and in descending order, in each of the fields: classroom management, methods and tools of education, addressing achievement problems, educational curriculum, evaluation of learners, professional development of teachers, while the lowest practices and a low degree were in the field of “supervision of teachers”. The results also showed that there were no statistically significant differences at the level of significance (0.05) between the scores of the teachers’ responses due to each of the variables: gender, number of years of experience, and the job status of the teacher, regarding the school principal’s practice of his role as a resident educational supervisor in each of the seven fields of the questionnaire. In the light of its findings, the study recommended the need to enroll principals of public intermediate schools in training programs to provide them with the competencies (knowledge - skills), that enable them to exercise their role as educational supervisors in residence effectively. The study also recommended the need to reduce the administrative burden on the school principal, and to provide the necessary financial and material resources, equipment and teaching aids for public schools.
Keywords: العملية التعليمية -- الإدارة المدرسية -- المشرف التربوي -- المدارس المتوسطة الرسمية